Ibn Miskawaih's Ethical Philosophy and Its Relevance to Moral Education in Indonesian Secondary Schools - Juwaini, Juwaini; Rijal, Syamsul; Basir @ Ahmad, Aminudin; Desky, Harjoni; Tamtowi, Moh; Mawardi, Mawardi; Safira, Cut Siska (Jurnal Ilmiah Peuradeun, 2025)
This study explores the application of Ibn Miskawaih’s ethical philosophy in shaping moral education in Indonesian secondary schools, focusing on Madrasah Aliyah (MA) and General Senior High Schools (SMA). Amid increasing concerns over student deviant behaviors—such as bullying, online gambling, and indiscipline—this research examines how Ibn Miskawaih’s framework, which emphasizes the harmonization of reason (al-Nathiqah), emotion (al-Ghadabiyyah), and instinct (al-Bahimiyyah), is operationalized in contemporary educational settings. Using a qualitative case study approach, data collection involved observations, interviews, and document analysis. Findings reveal distinct approaches: MA integrates religious mentoring and structured moral education, while SMA incorporates moral values within broader character education initiatives. However, both face challenges, including inconsistent parental involvement, weak supervision, and the absence of structured moral assessment tools. This study highlights the need for stronger school-family collaboration, enhanced supervision policies, and systematic moral evaluation instruments. By bridging classical Islamic ethical thought with contemporary education, this research provides valuable insights into the role of Ibn Miskawaih’s philosophy in addressing modern moral challenges and fostering holistic character development among students.